AJI BLEGODAWA TEXT IN THE PERSPECTIVE OF FUNCTIONAL SYSTEMIC LINGUISTICTS - Rasna, I Wayan; Suastra, Made; Sutjaja, I Gusti Made; Darma Laksana, I Ketut (e-Journal of Linguistics; Vol. 4. Januari 2010 No. 1, 2010)
This research give answers to the following five problems; they are (1) the lexico grammar of AjiBlegodawa Text (Text Aji Blegodawa; hereon abbreviated to TAB); (2) the context of situation (register)and the context of culture (genre) of TAB; (4) the ideational, interpersonal and textual meanings of TAB;and (5) the values in TAB. Note taking method was employed for collecting the data needed for thelexicogrammar, the context of situation, the functions, meanings, and the values. The data needed for thecultural context were collected by note taking, questionnaire, observation and structured interview.Structured interview, in which eleven informants were interviewed, was also employed for collecting dataneeded for the values. Functional system linguistics (hereon abbreviated to FSL) introduced by Hallidaywas employed to analyze the data (Halliday, 1985: 2004; 2005); (Halliday and Maththiessen, 2004).The findings show that the frequencies of the processes in the text are as follows: the materialprocess appears 674 times (52.29%); the relational process takes place 233 times (18.08%) and the mentalprocess occurs 177 (13.73%).With regard to circumstances, the circumstance of location is the most dominant followed by thecircumstance of manner. From the context of situation, it can be identified that the field is black magic;from the participants, it can be identified that the main participant is Blegodawa. The mode issimultaneously used to form the configuration of meaning. It can be revealed that the main participantsupported by the supporting participants kill the victim. Viewed from the cultural point of view, thecultural norms referred to in TAB destroy life. The linguistic functionsin TAB are: 1) ideational function which includes belief, the tradition of the magic world, taboo,historical relationship and ritual; 2) interpersonal function which includes interactive function and selfexpressive function and 3) textual function. The meanings in TAB include ideational meaning,interpersonal meaning and textual meaning. The values in TAB include: 1) the value of power (theintention to have the power) which is made up of a) religious value as the basis for having the intention tohave the power); b) the magic value as the basis for having the intention to have the power; c) the magicsocio cultural value as the basis for having the intention to have the power; 2) the achievement value (theintention of achieving something) as the basis for having the intention to achieve something magically; 3)the hedonism value and 4) the value of universalism.
Keywords: Text, Lexicogrammatical, Context of situation, Culture, Meaning and Value